Analysis of the Impact of Teaching Experience on Teacher Professionalism with Digital Literacy as an Intervening Variable at Elementary Schools in Bengkayang District, Bengkayang Regency - Hendrikus Torimtubun; Kusnanto Kusnanto; Siprianus Jewarut (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Teacher professionalism is a key factor in improving the quality of education, but the mechanisms of its formation in the era of digital transformation are not yet fully understood, especially at the elementary school level. This study aims to analyze the influence of teaching experience on teacher professionalism with digital literacy as an intervening variable. The study used a quantitative explanatory approach with a cross-sectional survey design. The sample in this study involved 138 teachers. Data were collected using a questionnaire with a five-point Likert Scale and analyzed using SEM-PLS. The research findings indicate that: teaching experience influences digital literacy. Teaching experience has a positive and significant effect on teacher professionalism. Digital literacy influences teacher professionalism. Digital literacy is proven to mediate the effect of teaching experience on teacher professionalism. The findings of partial mediation indicate that teaching experience influences teacher professionalism through two channels: directly and indirectly through increased digital literacy. This study confirms that the development of teacher professionalism in the Independent Curriculum era is not sufficient to rely solely on accumulated work experience, but must be accompanied by structured and sustainable strengthening of digital literacy. The practical implications of this research encourage schools to synergistically integrate digital literacy improvement programs with teacher teaching experience development programs.